Pankolitis Akibat Kolitis Ulseratif - Afifah Amatullah; Saptino Miro (Health and Medical Journal, 2021)
Introduction: Ulcerative colitis is a chronic disease affecting large intestine, characterized by rectal bleeding, diarrhea, abdominal pain, and could be accompanied by extraintestinal manifestation such as fever, anemia, and weight loss. Ulcerative colitis is causing an inflammation even ulceration of the rectum which can extend to proximal colon. The incidence of this disease is increasing worldwide and its frequency is variable depend on age, race and geographic area. Thorough history and examination are needed in diagnosing ulcerative colitis, since its symptoms are similar to many other gastrointestinal diseases. Definitive diagnosis of ulcerative colitis can be obtained by colonoscopy and histopathology. Case Report: We reported a case of 53 years old man who suffered from diarrhea and weight loss for one month before admission. There were also blood and mucus in his stool. The result of colonoscopy was hyperemia and ulcers along the rectum to the caecum. Histopathology examination showed pieces of intestinal mucosal tissue covered by columnar epithelium, with goblet cell and round-oval core. The lamina propria is densely packed with lymphocyte cells, plasma cells and PMN leukocytes. This result represents chronic colitis with acute exacerbation. Conclusion: Patient was treated with mesalazine 3x1000 mg per oral, methyl prednisolone 3x16 mg per oral, and low fiber diet to achieve remission.